The silicon trypanosome: a test case of iterative model extension in systems biology - Achcar, Fiona; Fadda, Abeer; Haanstra, Jurgen R.; Kerkhoven, Eduard J.; Kim, Dong-Hyun; Leroux, Alejandro E.; Papamarkou, Theodore; Rojas, Federico; Bakker, Barbara M.; Barrett, Michael P.; Clayton, Christine; Girolami, Mark; et al. (Advances in microbial systems biology, 2014)
The African trypanosome, Trypanosoma brucei, is a unicellular parasite causing African Trypanosomiasis (sleeping sickness in humans and nagana in animals). Due to some of its unique properties, it has emerged as a popular model organism in systems biology. A predictive quantitative model of glycolysis in the bloodstream form of the parasite has been constructed and updated several times. The Silicon Trypanosome is a project that brings together modellers and experimentalists to improve and extend this core model with new pathways and additional levels of regulation. These new extensions and analyses use computational methods that explicitly take different levels of uncertainty into account. During this project, numerous tools and techniques have been developed for this purpose, which can now be used for a wide range of different studies in systems biology.
Gesehen am 30.09.2020